Twenty thousand leagues under the sea - Verne, Jules, 1828-1905.; Miller, Ron, 1947- (Morris Plains, N.J. : Unicorn, 1989)
Professor Aronnax and his friends are captured by the mysterious Captain Nemo. An underseas tour, giant squids, and the lost city of Atlantis all appear on their voyages.
5.3
3-6
3-6
1030
Keywords: Submarines -- Fiction; Science fiction; Sea stories -- Fiction; Submarines -- Fiction; Science fiction; Sea stories -- Fiction